Psychoeducation for psychological issues and birth preparedness in low- and middle-income countries: a systematic review (2022)
BACKGROUND: Psychological issues usually accompany the pregnancy of first-time mothers, and psychoeducational interventions might be effective in addressing these concerns and preparing first-time mothers for childbirth and the postnatal period. OBJECTIVE: This study aimed to identify, analyze, and synthesize the components and determine the effectiveness of psychoeducational interventions that are used for managing psychological issues and enhancing birth preparedness among primigravid women or couples in low and middle-income countries. STUDY DESIGN: A systematic search of 12 databases (APA PsycINFO, EmCare, Embase, MEDLINE(R), Ovid Nursing, British Nursing Index, Health & Medical Collection, ProQuest, CINAHL, Cochrane, Hinari, and PubMed) was conducted to identify relevant studies published between 1946 and October 2021. The quality of the included studies was appraised by the Joanna and Briggs Institute critical appraisal tool, and a narrative synthesis was performed to analyze data extracted from included articles. The systematic review protocol is registered with the International Prospective Register of Systematic Reviews (registration number: CRD42021237896). RESULTS: The initial search yielded 8658 articles. Of note, 16 articles, including 7 randomized controlled trials and 9 nonrandomized trials, met the inclusion criteria and were selected and reviewed for quality. In addition, 31 outcomes were measured in the studies, including psycho logical outcomes, birth preparedness outcomes, and other outcomes. The design of the interventions included antenatal education that was delivered through lectures, role plays, trainings, and antenatal counseling. All the psychoeducational interventions had a significant effect (P<0.05) Cohen’s d or Hedges’ g=0.2−1.9) on certain psychological outcomes, including childbirth attitude, fear of childbirth, depression, fear, and anxiety, and birth preparedness outcomes. CONCLUSION: Although first-time mothers experience a range of psychological issues during pregnancy, psychoeducational interventions were beneficial in addressing their psychological concerns. It would seem that these interventions are less expensive and could be easily implemented in low- and middle-income countries. However, rigorous research, such as randomized controlled trials, is hereby warranted to standardize the interventions and outcome assessment tools.